Efficacy of Fungicides Against Rhizoctonia solani Inciting Rhizome Rot Diseases on Large Cardamom (Amomum subulatum Roxb.) - Karkee, Ajaya; Mandal, Dhanik Lal (International Journal of Applied Sciences and Biotechnology, 2020)
An in-vitro experiment was carried out for testing the efficacy of various fungicides by adopting poisoned bait method against Rhizoctonia solani (isolated from large cardamom) in Agricultural Research Station, Pakhribas. The experiments were conducted with Completely Randomized Design (CRD) during 2016 with four replications. Two level of concentration of the fungicides (10 ppm and 100 ppm) were used and concentration was calculated based on active ingredients (a.i.) of the pesticides. At lower concentration (10 ppm), Nativo (Tubeconazole 50% + Trifloxystrobin 25 WG) and Dhanustan (Carbendazim 50 % WP) whereas at higher concentration (100 ppm), Folicure (Tubeconazole 25.9 %) and Saaf (Carbendazim 12 % + Mancozeb 63 % WP) found effective for the inhibitions of mycelia growth of R. solani. For the control of R. solani, Nativo and Dhanustan showed greatest inhibition of mycelia growth at 10 ppm concentration as compared to other fungicides. The fungicides containing Tubeconazole and Carbendazim as active ingredients, shows highest degree of mycelia inhibitions as compared to others. The fungicides found effective for inhibition of mycelia growth of R. solani in this study should be further tested in field conditions to verify their efficacy as well as to determine their optimum doses of application.Int. J. Appl. Sci. Biotechnol. Vol 8(1): 61-64